Supply chain and net margin analyses of abaca from Brgy. Panibasan, Maco, Compostela Valley Province - Merced, Damsel Ebbe T.
Abaca is one of the natural fibers that can be found in the Philippines and is considered as a high-valued industrial crop. Philippines is the major producer of the crop in the world particularly in the Eastern Visayas Region. In addition, Mindanao is also competitive in terms of the volume produced especially the Davao Region which ranked as the 3rd largest producer. Herewith, the supply chain and net margin analyses were done to map out and study the flow of the abaca fibers from Brgy. Panibasan, Maco, Compostela Valley, and assess the distribution of benefits of the key players across the chain. Supply analysis was also used to determine the factors that greatly affect the production in the area. Results show that supply chain of abaca in the area is short and simple wherein the key players are the farmers, barangay trader, wholesaler, the processors, and the retailer. It was discovered that the farmers in Brgy. Panibasan are price-takers, the buyers have the control over the price. Farmers usually deliver their produce to the town trader, but when their harvest is lower than the usual they sell it to the barangay traders. On the other hand, results of net margin analysis depict that the town trader received the most benefit since they control the farmgate price for abaca fibers and the farmers oftentimes incur losses. Using supply analysis, it was found that labor cost is the most significant factor that could affect the supply. Thus, the higher the labor cost is, the lower the profit they will get.